Sources of knowledge empowerment amongst pregnant women with TB disease: A qualitative study in South Africa - Mulondo Seani Adrinah; Khoza Lunic Base; Lebese Rachel Tsakani (Wiley, 2024)
Abstract Background Providing relevant knowledge to empower all pregnant women diagnosed and nondiagnosed with tuberculosis (TB) is essential worldwide. Proper dissemination of health information for pregnant women could assist in preventing TB complications amongst women and babies. The study aimed to describe the sources of knowledge that empower pregnant women diagnosed with TB and improve their quality of life in Limpopo Province, South Africa. Methodology The study followed a qualitative, exploratory and descriptive research design. The study was conducted in 12 selected primary healthcare facilities in three crisis districts. Thirty‐five pregnant women with TB disease were purposively selected, and face‐to‐face interviews were conducted to generate data, which were analysed using the thematic approach. Measures to ensure trustworthiness and ethical standards were adhered to. Results The findings of this study revealed that healthcare workers, community stakeholders, and TB ambassadors are the primary sources of knowledge dissemination for capacitating women diagnosed with TB. Conclusion Most pregnant women lacked knowledge regarding TB ambassadors as sources of information for empowering women, community awareness campaigns, and Google searches as sources of information sharing. All stakeholders need to work together, considering the patients' charter for TB care that sets out the right for respect and information sharing. The emphasis of this study was on developing a comprehensive educational intervention that could assist in improving the quality of TB services offered to pregnant women.